A System Analysis and Design of Purple Sweet Potatoes Porridge Product Development - Ani Nuraisyah (Universitas Darussalam Gontor, 2020)
A system analysis and design of purple sweet potatoes instant porridge product developmentis design elements that interact using the system input of purple sweet potatoesas raw material which is operated by the stage of formulation, analysis, and optimization. The purpose of this research are determine the appropriate process parameters in producing purple sweet potatoes instant porridge, as well as to optimize the proportion of components in the production of purple sweet potatoes instant porridge, which are the purple sweet potatoes as raw material, water,CMC and dextrin; those which affect the responses: yield, rehydrating capacity, voluminous density and stickiness in the mouth.Production system modeling purple sweet potatoesinstant porridge simulated using and Business Process Modeling Notation (BPMN). The result of analysis are the proportion of purple sweet potatoesinstant porridge components; which is purple sweet potatoes, water, CMC and dextrin, has significant effect on the level of 5% to the responses of yield, capacity rehydration, voluminous density, and stickiness in the mouth. The optimization process generates the formula for instant porridge with proportion of 25.00% purple sweet potatoes, 73.03% water, 0.00% CMC and 1.97% dextrin to the value of desirability 0.662. The parameters contained in the model were validated by checking the model design. The validation result with no error and warning concluded that the parameters used in designing the model are appropriate.